2017
DOI: 10.1016/j.addbeh.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the perceived effectiveness of pregnancy-related cigarette package health warning labels among different gender/age groups

Abstract: Introduction The impact of pregnancy-related health warning labels (HWLs) appearing on cigarette packages on women of reproductive age and other socio-demographic groups is not well understood. The current study analyzes how different age/gender groups respond to pregnancy-related HWLs as compared to non-pregnancy HWLs. Methods Data were analyzed from four waves of an online longitudinal study with adult smokers aged 18-64 in Australia, Canada, Mexico, and the US. Participants were classified into four age\g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 23 publications
3
24
1
Order By: Relevance
“…The percentage of smokers in this group was lower than for the aforementioned messages that targeted a broader audience, yet more than half of smokers still found at least one of these reproductive health messages to be effective (58%). As expected, younger smokers were more likely to be in this group than to be unaffected, likely because of message relevance for people of reproductive age; however, females and males were equally likely to be affected, inconsistent with results for loss-frame messages on reproductive health that showed stronger responses among females [ 28 ]. This may be because men were mentioned in at least some, although not all, of the messages evaluated, therefore providing them with relevant content that is often not present in warning labels.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The percentage of smokers in this group was lower than for the aforementioned messages that targeted a broader audience, yet more than half of smokers still found at least one of these reproductive health messages to be effective (58%). As expected, younger smokers were more likely to be in this group than to be unaffected, likely because of message relevance for people of reproductive age; however, females and males were equally likely to be affected, inconsistent with results for loss-frame messages on reproductive health that showed stronger responses among females [ 28 ]. This may be because men were mentioned in at least some, although not all, of the messages evaluated, therefore providing them with relevant content that is often not present in warning labels.…”
Section: Discussionmentioning
confidence: 86%
“…Concordance between a message and its recipient may also be due to the textual content of the message. For example, some research has found that cigarette warnings about pregnancy-related harms from smoking are rated as more effective by women of reproductive age than by other groups [ 28 ]. Efficacy messages about cessation benefits and quitting tips may be more relevant and effective for smokers who intend to quit or have recently tried to quit, as found for pictorial warnings that generally use loss-framed messages [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analyses regarding Set A pictorial HWLs indicated that females reported greater perceived effectiveness of the benign HWLs, which may reflect literature suggesting that women are more likely to consider quitting after viewing labels [ 31 , 42 , 43 ] and may be responsive to a broader range of pictorial HWLs, particularly those not using gruesome imagery [ 33 ]. It is important to note that two of these HWLs may be particularly relevant to women, one regarding the impact on fetuses and on appearance [ 12 , 32 ]. The finding that living in a rural area was associated with greater perceived effectiveness of these messages may reflect prior lack of exposure to such messaging, thus promoting more intentional processing of the information, as prior research suggests [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other evidence suggests that younger people may perceive HWLs effective that depict the cosmetic consequences of smoking including rotten teeth, premature skin aging, or wrinkled skin [ 12 ]. In addition, female smokers are more likely than male smokers to consider quitting after looking at a pictorial HWL [ 31 ], women of reproductive age are more responsive to pictorial HWLs about pregnancy [ 32 ], and women are more likely than men to perceive pictorial HWLs with non-gruesome content, such as those depicting a human experience related to smoking, as more effective [ 33 ]. Moreover, people in rural areas have a lower general awareness of all forms of tobacco information, including HWLs [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perceived effectiveness has been used to examine a range of behavior change issues, including promotion of hand hygiene [ 47 ], pregnancy-related cigarette package health warnings [ 48 ], physical activity apps [ 49 ], image of green products [ 50 ], feeling of connectedness [ 51 ], traffic control [ 52 ], etc. However, there are only several scholars that investigated the link between perceived effectiveness and actual effectiveness.…”
Section: Introductionmentioning
confidence: 99%